Pemberdayaan Kelompok Tani Giat Bakti Lestari Desa Cibadung Gunung Sindur melalui Pelatihan Teknologi Kultur Jaringan Menuju Petani Modern - Fitri Damayanti; Acep Musliman; Andri Suryana; Hasbullah Hasbullah; Sarah Imsakiah Harahap; Ahla Safira Maulida (BADAN PENERBIT STIEPARI PRESS, 2025)
The Community Partnership Empowerment (PKM) program was conducted with the “Giat Bakti Lestari” Farmer Group in Cibadung Village, Gunung Sindur, Bogor. Partners faced two main problems: low banana harvest quality caused by Fusarium wilt disease and the presence of idle, unproductive land. As a solution, the PKM team introduced banana propagation using tissue culture technology through socialization, training, and mentoring. This method offers several advantages over conventional propagation, including faster cultivation, mass production, disease-free seedlings, and genetic uniformity. However, partners had no prior exposure to tissue culture technology. Thus, the PKM activity focused on equipping farmers with skills in household-scale tissue culture techniques and providing simple facilities to support sustainable seedling production. By engaging in this program, the farmer group is expected to gain essential knowledge and practical skills, enabling them to independently manage tissue culture propagation. This initiative not only addresses crop loss due to disease but also promotes the use of modern agricultural practices to maximize land productivity. The activity ultimately aims to foster self-reliance among farmers and contribute to the development of innovative an sustainable farming in the village.